Beyond relationship quality: The role of leader–member exchange importance in leader–follower dyads. Issue 4 (2nd March 2019) - Lee, Allan; Thomas, Geoff; Martin, Robin; Guillaume, Yves; Marstand, Anders F.
Abstract : In this paper, we introduce a novel construct, leader–member exchange (LMX) importance, which we position as a meta‐perception indicating whether followers view their LMX relationship as personally important or valuable to them. Based on social exchange theory, we examine the extent to which the obligation followers feel towards their leader depends jointly on the quality and the importance of the LMX relationship. We examine how LMX importance influences the process through which LMX quality affects employees' level of organizational citizenship behaviour (OCB) by focusing on felt obligation (a measure of followers' reciprocity obligation in the social exchange process) as a mediating variable. Across two studies, we found that high levels of both LMX quality and LMX importance interacted to engender a greater feeling of obligation in followers to repay the perceived favourable exchanges with their leader. Felt obligation predicted leader‐rated OCB, demonstrating support for our hypothesized moderated mediation model. However, psychological empowerment, when included alongside felt obligation (in Study 2), did not mediate the LMX‐OCB relationship. Overall, our findings extend the focus of LMX theory beyond the confines of LMX quality to incorporate the importance of the LMX relationship. Practitioner points: Leaders should be aware that followers vary in the extent to which they perceive the leader–follower relationship to be personally important. As such, they may decide to invest heavily in helping followers understand that the relationship is instrumental for their success at work. Leaders should invest not only in trying to build positive relationships, but also in establishing the importance of these relationships. Doing so will maximize the benefits of developing a high‐quality relationship. Followers appear to be more willing to reciprocate when they perceive a high‐quality relationship with the leader and one when they perceive the relationship to be important. Thus, managers should be aware that the norm of reciprocity may vary depending on how important followers perceive the relationship to be and leaders may need to find other ways to motivate employees who do not see the relationship as important. When followers do not see the leader–follower relationship as important, managers should avoid trying to engage in reciprocity contingent influence tactics and/or try to change followers' perceptions of the importance of the relationship.